Influence of grain processing products on the indicators of frozen milkprotein mixtures - Tsygankov, Sergii; Ushkarenko, Viktor; Grek, Olena; Tymchuk, Alla; Popova, Inna; Chepel, Natalia; Onopriichuk, Olena; Savchenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports a study into the influence of manna groats and extruded manna groats on the qualitative and quantitative indicators of milk and protein concentrates over a freezing–defrosting cycle. A slight change in the quality of proteinplant mixtures after defrosting confirms the cryoprotective properties of carbohydrates of plant components. The capability to preserve albumin mass at negative temperatures with its subsequent use as the milkprotein basis for semifinished products was proven. The feasibility of using a collagencontaining ingredient in the amount of 0.4 % for the intensification of the thermalacid coagulation of whey proteins was proven experimentally. The process was performed both in native whey and in protein concentrate with a mass fraction of dry substances of (16±2) %, obtained by the ultrafiltration method. It was revealed that coagulation duration is (55±2) min and (40±2) min, respectively, at a temperature of (95±2) °C. A decrease in the duration of the process correlates with a decrease in power consumption. Adding albumin mass, in addition to cottage cheese, to the formulation of semiproducts would increase milk protein resources. We report results of research into cryoscopic temperature of mixes based on cottage cheese with manna groats and extruded manna groats, as well as of the albumin mass obtained with the use of “Collagen pro 4402”. The amount of frozen moisture in milk and protein mixtures with wheat processing products was determined by the calculation method. It was proven that the modification of the carbohydrate complex of grains by means of extrusion ensures an increase in binding free moisture in proteinplant mixtures during defrosting